A COMPARATIVE STUDY OF THE EFFECTS OF THE NEUROCOGNITIVE-BASED MODEL AND THE CONVENTIONAL MODEL ON LEARNER ATTENTION, WORKING MEMORY AND MOOD (Malaysian Journal of Learning and Instruction, 2017)
Purpose â€“ The attention, working memory, and mood of learners are the most important abilities in the learning process. The importance of these abilities has led the researchers to undertake the present study. This study was concerned with the comparison of contextualized attention, working memory, and mood through a neurocognitive-based model (5P) and a conventional model (5E). It sought to examine the significant change in attention, working memory, and mood of Grade 9 students after the intervention of a neurocognitive-based model (5P) and a conventional model (5E) in an experimental group and a control group, respectively.Methodology â€“ A total of 76 out of 324 Grade 9 students were randomly selected from a high school located in Mahasarakham province, Thailand. A pre-test and post-test control group design was employed. The neurocognitive-based model (5P) was developed utilizing a neurocognitive-based theory and was implemented in the experiment group, while the conventional model (5E) was used in the control group. Three types of psychological tests were utilized as research instruments, namely the attention computerized battery test, the working memory computerized battery test, and the Bond-Ladder visual analogue scale. MANOVA analysis was used to analyse the effect of these instructional models on student attention, working memory, and mood in Grade 9. Findings â€“ The findings revealed that the overall attention, working memory, and mood conditioning mean score of the neurocognitivebased model (5P) interventions were better than in the conventional model. In conclusion, the results revealed that neurocognitive based contextualization had more effect on the attention, working memory, and mood of Grade 9 students than conventional model (5E) contextualization.Significance â€“ The findings have contributed significantly to current knowledge on the effectiveness of the neurocognitive-based model (5P) to enhance student learning outcomes in terms of attention, working memory and mood.